Hurricane Katrina and the Lessons of Disaster Relief. - Powelson, Michael (Cambridge Scholars Publishing, 2017)
Hurricane Katrina, which hit the Gulf Coast in 2005, exposed the failings and incompetence of local, state, and federal officials, as well as the private sector and a host of other public and private agencies. This volume explores how inaction, lack of planning and undisguised greed insured that a category 3 hurricane would result in widespread destruction of both lives and property. It adopts a multifaceted approach to Hurricane Katrina, and includes studies from the fields of oral history, environmental science, physics, political science, sociology, and history. Part One provides first-hand.